Time from Earth rotation to atomic physics - McCarthy, Dennis D.; Seidelmann, P. Kenneth 1937- (Cambridge University Press, 2018)
In the twenty-first century, we take the means to measure time for granted, without contemplating the sophisticated concepts on which our time scales are based. This volume presents the evolution of concepts of time and methods of time keeping up to the present day. It outlines the progression of time based on sundials, water clocks, and the Earth's rotation, to time measurement using pendulum clocks, quartz crystal clocks, and atomic frequency standards. Time scales created as a result of these improvements in technology and the development of general and special relativity are explained. This second edition has been updated throughout to describe twentieth- and twenty-first-century advances and discusses the redefinition of SI units and the future of UTC. A new chapter on time and cosmology has been added. This broad-ranging reference benefits a diverse readership, including historians, scientists, engineers, educators, and it is accessible to general readers